The development of e-profiling website in supporting socio-literacy for an organization by using case based reasoning - Nur Hidayah, Baharim (2019)
Human hold a different kind of personality type that act diversely. According to Ernest Tupes and Raymond Christal, there are big five (5) personality model called OCEAN which represents Openness, Conscientiousness, Extraversion, Agreeableness and Neuroticism. Each personality owned a different criteria and specific explanation towards their behavior. Thus, this different personality build a tremendous diversity in an organization. Recently, there are some issues arises in an organization for instance, miscommunication among colleague, misperception, discrimination, mitigation in work productivity and less job satisfaction occur due to have a different norm of personality and wrong choices of career path. Therefore, the aim of this research is to develop a e-profiling website in supporting socio-literacy for an organization which is based on the premise that if experiences from the user personality can be captured in some useful form, the tool will able to propose the solution in having good interaction inside the organization. Hence, this research will implement the Case Based Reasoning (CBR) technique that able to give a solution to improve the relationship between the colleagues and guide the staff to polish, monitor and improve the strength of each individual specifically and organization holistically. This approach will assist the decision-makers of the organization by propose the solutions in reusing or revising the solutions from similar cases and from their past experiences.